Association of Perfluoroalkyl and polyfluoroalkyl substances (PFASs) exposures and the risk of systemic lupus erythematosus: a case-control study in China - Yan He; Can Qu; Jing Tian; Justyna Miszczyk; Hua Guan; Ruixue Huang (BMC, 2023)
Abstract Perfluoroalkyl and polyfluoroalkyl substances (PFASs) may have a role in impaired health. However, the data on the association between PFASs and Systemic lupus erythematosus (SLE) have been limited. We designed a population-based case-control study in China and evaluated the association. 100 normal persons (Control) and 100 SLE patients (Case) were obtained from 113 controls and 125 cases according to matching conditions. Serum samples were collected by venipuncture for UHPLC-MRM-MS Analysis to obtain the concentration of five PFASs in participants. Demographic characterization description was performed for the two groups of participants, the PFASs concentration distribution of the two groups was described and compared, then divided into three tiers (< 50th, 50th ~ 75th, > 75th) for subsequent analysis. Conditional logistic regression models were utilized to calculate the odds ratios (ORs) and 95% CIs for SLE. Relationship between changes in the concentration of PFASs and the risk of SLE assessed by restricted cubic spline. As the highest serum levels of the five PFASs tested in this study population, the highest perfluoroundecanoic acid (PFUnA) quartile had a 2.78-fold (95%CI: 1.270, 6.10) compared with the lowest quartile of PFUnA exposure, other types of PFASs also showed high association with SLE as well as PFASs mixture. Additionally, the exposure of PFASs exist a dose-response relationship (ptrend < 0.05). This risk association remained be found after adjusting the covariates in model 1 (adjustment of BMI) and in model 2(adjustment of BMI, smoking, drinking, hypertension and leukocyte). The restricted cubic spline illustrated a gradual increase in the possible risk of SLE with the increasing exposure of PFASs components levels. Our study firstly revealed that PFASs are risk factors for SLE and PFASs exposures are associated with SLE risk in a dose − response manner. Evidence from larger and more adequately powered cohort studies is needed to confirm our results.